Differential projections from the cochlear nucleus to the inferior colliculus in the mouse - Ryugo, David K.; Milinkeviciute, Giedre (Frontiers in Neural Circuits, 2023)
The cochlear nucleus (CN) is often regarded as the gateway to the central auditory system because it initiates all ascending pathways. The CN consists of dorsal and ventral divisions (DCN and VCN, respectively), and whereas the DCN functions in the analysis of spectral cues, circuitry in VCN is part of the pathway focused on processing binaural information necessary for sound localization in horizontal plane. Both structures project to the inferior colliculus (IC), which serves as a hub for the auditory system because pathways ascending to the forebrain and descending from the cerebral cortex converge there to integrate auditory, motor, and other sensory information. DCN and VCN terminations in the IC are thought to overlap but given the differences in VCN and DCN architecture, neuronal properties, and functions in behavior, we aimed to investigate the pattern of CN connections in the IC in more detail.This study used electrophysiological recordings to establish the frequency sensitivity at the site of the anterograde dye injection for the VCN and DCN of the CBA/CaH mouse.We examined their contralateral projections that terminate in the IC. The VCN projections form a topographic sheet in the central nucleus (CNIC). The DCN projections form a tripartite set of laminar sheets; the lamina in the CNIC extends into the dorsal cortex (DC), whereas the sheets to the lateral cortex (LC) and ventrolateral cortex (VLC) are obliquely angled away. These fields in the IC are topographic with low frequencies situated dorsally and progressively higher frequencies lying more ventrally and/or laterally; the laminae nestle into the underlying higher frequency fields. The DCN projections are complementary to the somatosensory modules of layer II of the LC (Lesicko et al., 2016) but both auditory and spinal trigeminal terminations converge in the VLC (Zhou and Shore, 2006). While there remains much to be learned about these circuits, these new data on auditory circuits can be considered in the context of multimodal networks that facilitate auditory stream segregation, signal processing, and species survival.